2019
DOI: 10.1371/journal.pone.0221163
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling identifies a novel compound with antidepressant properties

Abstract: Patients with traumatic brain injury (TBI) are frequently diagnosed with depression. Together, these two leading causes of death and disability significantly contribute to the global burden of healthcare costs. However, there are no drug treatments for TBI and antidepressants are considered off-label for depression in patients with TBI. In molecular profiling studies of rat hippocampus after experimental TBI, we found that TBI altered the expression of a subset of small, non-coding, microRNAs (miRNAs). One kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In recent years, many researchers have reported that non-coding RNAs play an important role in maintaining stable and normal NVU function. MicroRNAs (miRNAs) are short (19)(20)(21)(22)(23)(24)(25)(26)(27)(28) nucleotides) endogenous non-coding RNAs that regulate protein synthesis at the post-transcriptional level 16 . Previous studies have verified that the levels of various miRNAs are significantly changed in brain tissues after TBI, which can restore the normal function of the NVU by inhibiting the apoptosis of neurons and reducing the destruction of the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many researchers have reported that non-coding RNAs play an important role in maintaining stable and normal NVU function. MicroRNAs (miRNAs) are short (19)(20)(21)(22)(23)(24)(25)(26)(27)(28) nucleotides) endogenous non-coding RNAs that regulate protein synthesis at the post-transcriptional level 16 . Previous studies have verified that the levels of various miRNAs are significantly changed in brain tissues after TBI, which can restore the normal function of the NVU by inhibiting the apoptosis of neurons and reducing the destruction of the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the single-nuclei sequencing dataset GSE137869 [ 10 ] was retrieved for cell marker identification. Among the datasets, GSE2871 [ 11 ] was used for WGCNA; GSE2392 [ 12 ], GSE2871 [ 11 ], and GSE45997 [ 13 ] were used in the GSEA analysis; GSE1911 [ 14 ], GSE2392 [ 12 ], GSE24047 [ 15 , 16 ], GSE31357 [ 17 ], GSE59645 [ 18 ], GSE64978 [ 19 ], GSE67836 [ 20 ], GSE68207 [ 19 ], GSE80174 [ 21 ], GSE86579 [ 22 ], GSE111452 [ 23 ], and GSE115614 [ 18 ] were analyzed for validation. Among the samples in the above datasets, only samples from wild-type rats with no additional treatment or disease other than TBI were included.…”
Section: Methodsmentioning
confidence: 99%
“…Fresh frozen sections were post-fixed for 20 min in 4°C paraformaldehyde, incubated overnight with 1 o antibody (mouse anti-CD11b; 1:2000), the following morning incubated with a 2 o antibody (Alexa 594 goat anti-mouse; 1:400) at ambient temperature, and then mounted with nuclear stain DAPI for imaging. Detailed procedure available in Sell et al, [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…Like many thousands of researchers who are engaged in elucidating the underlying mechanisms of and finding therapeutic treatments for traumatic brain injury (TBI) [ 1 – 3 ], we have extensively used animal models of TBI to study the underlying molecular mechanisms [ 4 , 5 ] and importantly, to test several experimental compounds for potentially neuroprotective effects [ 6 8 ]. However, the lesson we have learned from two decades of extensive in vivo studies is that evaluating novel compounds for neuroprotective effects in animal models of TBI is a protracted, labor-intensive and costly endeavor with no guarantee of success.…”
Section: Introductionmentioning
confidence: 99%